Digital Barriers to the Construction of China's Digital Villages and Countermeasures - Jiang Hu, Yiwen Wang (Forest Chemicals Review, 1970)
In recent years, the digital economy has flourished in China, and the convergence of new technologies such as big data and cloud computing has promoted the rapid development of the Internet of Things, bringing rare development challenges and opportunities to the construction of China's countryside. Some new digital information technologies are gradually integrated into China's agricultural and rural production, and the agricultural economy continues to increase its productivity and value, and the digital economy has become an important force in the development of digital countryside and digital agriculture. Although the current rural information service system is accelerating its construction and development and gradually improving, there are also problems such as digital divide, weak infrastructure and insufficient resources such as technicians. In order to develop rural areas, it is urgent to deeply explore the great potential of digital countryside in the development of digital economy, and to avoid harm in order to accelerate the process of rural construction, so that agriculture can be upgraded, infrastructure can be improved, farmers can be developed, and the overall progress of rural areas can be promoted. In this paper, on the basis of the important theories of digital countryside, we take agriculture, rural areas and farmers as the research objects, build an evaluation index system based on digital perspective, evaluate the development level of digital countryside by using the entropy-weighted TOPSIS method and use the obstacle degree model to focus on diagnosing the obstacle factors in the actual work of digital countryside construction, and propose corresponding countermeasures to overcome them with the results of empirical analysis. The research results show that the development progress of China's digital countryside construction from 2015 to 2019 is obvious, and the comprehensive evaluation value has increased from 0.039 to 0.952 in five years, and the digital countryside development has moved from a poor level to an increasingly good development level. The most important digital barriers affecting the digital countryside construction from 2015 to 2019 are the proportion of non-Internet users in rural areas and the scale of rural Internet users. Overall, the level of agricultural production is the most obvious obstacle to the development of digital countryside, and the construction of digital countryside should continue to promote the development of "Internet+" modern agriculture, enhance the application of new digital information technology in agriculture, and continuously improve the digital level of agricultural production.